ANALYSIS OF NEUTRON FIELDS GENERATED IN SPALLATION TARGETS OF B-URAN EXPERIMENTAL ASSEMBLY USING MONTE CARLO METHOD - Ondřej Šťastný; Miroslav Zeman; Dušan Král; Karel Katovský; Elmira Melyan; Jindřich Adam; Alexander Alexandrovich Solnyshkin (Acta Polytechnica CTU Proceedings)
The aim of this paper is to introduce experimental assembly B-URAN and the results of Monte Carlo simulations of neutron fields, which will be generated by using various spallation targets. This experimental assembly was constructed in Joint Institute of Nuclear Research in Dubna, Russian Federation, in order to study accelerator driven systems fundamental characteristics. Beam of 660 MeV protons should be used for that purpose. The MCNP model of such set-up has been developed at Brno University of Technology, Czech Republic. The goal is to get data needed for prediction of reaction rates in detectors placed in B-URAN experimental channels. Such data will be experimentally validated later. Furthermore, simulations of radiation exposure around this xperimental assembly were performed.